2010
DOI: 10.1111/j.1472-765x.2010.02969.x
|View full text |Cite
|
Sign up to set email alerts
|

Multi-walled carbon nanotubes/epilson-polylysine nanocomposite with enhanced antibacterial activity

Abstract: Aims:  To develop a new nano‐composite of multi‐walled carbon nanotubes (MWNTs) with enhanced antimicrobial activity. Methods and Results:  A novel antimicrobial nanocomposite [MWNT‐epilson‐polylysine (MEPs)] was synthesized via covalent attachment of epilson‐polylysine on MWNTs with hexamethylene diisocyanate (HDI) as the coupling agent. UV‐visible spectra and Fourier transform infrared spectra (FT‐IR) investigations indicate that MEPs is stable, with epilson‐polylysine leaching effectively eliminated. When c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…Meanwhile, CNT illustrated valuable activity against bacteria of digestive system. Decorating different functional groups on the CNT structure proved that the antimicrobial activity increased than that of pristine one . Adding conventional antibacterial agents like amoxicillin on the CNT structure could enhance the antimicrobial performance .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Meanwhile, CNT illustrated valuable activity against bacteria of digestive system. Decorating different functional groups on the CNT structure proved that the antimicrobial activity increased than that of pristine one . Adding conventional antibacterial agents like amoxicillin on the CNT structure could enhance the antimicrobial performance .…”
Section: Introductionmentioning
confidence: 99%
“…To develop the antimicrobial activity of CNT, they were functionalized with various functional groups such as metallic NPs and biochemical functionalities . Despite these materials are more active disinfectants, they showed that are unstable and separate from the main structure, easily …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Zhou and Qi48 synthesized MWCNTÀepilsonÀpolylysine (MEP) via covalent attachment of epilsonÀpolylysine on MWCNTs with hexamethylene diisocyanate as the coupling agent. At 20 mg L À1 , the antimicrobial activity of MEPs towards E. coli, Pseudomonas aeruginosa and Staphylococcus aureus increased by 72.1%, 64.5% and 69%, respectively, compared to those of unmodi¯ed MWCNTs.…”
mentioning
confidence: 99%